2015
DOI: 10.1139/cjp-2014-0025
|View full text |Cite
|
Sign up to set email alerts
|

Structural, dielectric, and multiferroic properties of (Bi0.5K0.5)(Fe0.5Nb0.5)O3

Abstract: A polycrystalline sample of (Bi 0.5 K 0.5 )(Fe 0.5 Nb 0.5 )O 3 was prepared using a mixed oxide at 1000°C. The preliminary structural analysis using X-ray diffraction data of the compound indicates the formation of a single-phase rhombohedral structure similar to that of parent BiFeO 3 . Microstructural and elemental analysis using a scanning electron micrograph and energy-dispersive X-ray spectroscopy, respectively, were carried out at room temperature with higher magnification exhibiting a uniform distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The lattice constant increased with increasing Zr content because the ionic radii of Fe 3+ (64 pm) are smaller than that of Zr 4+ (86 pm) and might be due to the changes in cation degree of Zr as compensation of electric charge. The average crystallite size was calculated based on Scherrer's method [9]:…”
Section: X-ray Diffraction Analysismentioning
confidence: 99%
“…The lattice constant increased with increasing Zr content because the ionic radii of Fe 3+ (64 pm) are smaller than that of Zr 4+ (86 pm) and might be due to the changes in cation degree of Zr as compensation of electric charge. The average crystallite size was calculated based on Scherrer's method [9]:…”
Section: X-ray Diffraction Analysismentioning
confidence: 99%
“…The n value represents the degree of interaction between the charge carriers and the surrounding environment; typically, this universal behavior of the n value ranges between 0 and 1, suggesting that conduction occurs through hopping . On the other hand, several previous studies have reported n values greater than 1 . According to Papathanassiou et al, there is no physical argument to restrict the n value to less than 1 at the empirical universal law of Jonscher.…”
Section: Resultsmentioning
confidence: 99%
“…Z´ values for all temperatures converging at higher frequency zone indicating a temperature and frequency independent behavior of the material in that frequency range. This may be due to the release of space charges, as a result of reduction in barrier properties of the material with rise in temperature [17], [19]. Further, the decreases of Z´ values with the temperature increase at low frequency shows a negative temperature coefficient of resistance (NTCR), which is a very distinctive property that semiconductors possess in some range of temperature [19], [17], [20].…”
Section: Impedance Spectroscopy (Is)mentioning
confidence: 99%
“…This may be due to the release of space charges, as a result of reduction in barrier properties of the material with rise in temperature [17], [19]. Further, the decreases of Z´ values with the temperature increase at low frequency shows a negative temperature coefficient of resistance (NTCR), which is a very distinctive property that semiconductors possess in some range of temperature [19], [17], [20]. The variation of the imaginary part of impedance Z with frequency at different temperatures for TiO2 sample is showed in Figure 4, it is observed that the Z´´ value increases with increasing the frequency reaching a maximum peak Z´´max called relaxation frequency, and then decreases with increasing in frequency.…”
Section: Impedance Spectroscopy (Is)mentioning
confidence: 99%
See 1 more Smart Citation